A Multicentric, Open-Label, Randomized, Comparative Clinical Trial of Two Different Doses of Expanded hBM-MSCs Plus Biomaterial versus Iliac Crest Autograft, for Bone Healing in Nonunions after Long Bone Fractures: Study Protocol. (22nd February 2018) - Gómez-Barrena, Enrique; Padilla-Eguiluz, Norma G.; Avendaño-Solá, Cristina; Payares-Herrera, Concepción; Velasco-Iglesias, Ana; Torres, Ferran; Rosset, Philippe; Gebhard, Florian; Baldini, Nicola; Rubio-Suarez, Juan C.; García-Rey, Eduardo; Cordero-Ampuero, José; et al.
Abstract : ORTHOUNION is a multicentre, open, comparative, three-arm, randomized clinical trial (EudraCT number2015-000431-32 ) to compare the efficacy, at one and two years, of autologous human bone marrow-derived expanded mesenchymal stromal cell (hBM-MSC) treatments versus iliac crest autograft (ICA) to enhance bone healing in patients with diaphyseal and/or metaphysodiaphyseal fracture (femur, tibia, and humerus) status of atrophic or oligotrophic nonunion (more than 9 months after the acute fracture, including recalcitrant cases after failed treatments). The primary objective is to determine if the treatment with hBM-MSCs combined with biomaterial is superior to ICA in obtaining bone healing. If confirmed, a secondary objective is set to determine if the dose of 100 × 10 6 hBM-MSCs is noninferior to that of 200 × 10 6 hBM-MSCs. The participants (n = 108 ) will be randomly assigned to either the experimental low dose (n = 36 ), the experimental high dose (n = 36 ), or the comparator arm (n = 36 ) using a central randomization service. The trial will be conducted in 20 clinical centres in Spain, France, Germany, and Italy under the same clinical protocol. The confirmation of superiority for the proposed ATMP in nonunions may foster the future of bone regenerative medicine in this indication. On the contrary, absence of superiority may underline its limitations in clinical use.